Exploring environmental factors that trigger carotenoid production and their effect on the biophysical properties of Staphylococcus aureus bilayer membranes (2022)
In this research we investigate In recent years, entities such as the World Health Organization have declared an emerging crisis owing to antibiotic resistance, causing an increasing number of untreatable diseases due to rapid evolution and resistance of bacteria due to misuse of antibiotics. A biofilm is a survival strategy of some microorganism to adapt to the environment, especially in combative conditions such as clinical spaces. This strategy allows the bacteria to become resistant and tolerant to different environmental stress factors such as antibiotics and osmotic stress, becoming serious public health problems. Biofilms are an assembly of bacterial cells that adhere to a surface. In this research project, a biofilm made of Staphylococcus aureus bacteria in clinical catheters will be studied, following up on previous research regarding biofilms that show a drastic and intriguing reduction of carotenoid levels in the catheter biofilm under flow conditions at 37 ºC, which leads to a reduction of lipid packing and a decrease in membrane rigidity at this temperature . This inhibition of carotenoid production demonstrates that carotenoids are only synthesized under exposure to particular stress factors that are not present in the catheter and that are still unknown. It is critical to understand under what conditions is the expression of carotenoids triggered in biofilms, since they may play a role in resistance to different antimicrobial agents. In this thesis we explore the role of oxygen as a stress factor that triggers the expression of carotenoids, and how the synthesis of carotenoids influences the biophysical properties of Staphylococcus aureus membranes in biofilms.